THE INFLUENCE OF FINANCIAL INCLUSION, FINANCIAL ACCESS, AND FINANCIAL ATTITUDE ON BUSINESS GROWTH AND ITS IMPACT ON THE WELFARE OF UMKM IN JAMBI CITY - Putri, Resame; Putra, Wirmie Eka; Erwati, Misni (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This study aims to explore the influence of financial inclusion, financial access, and financial attitude on business growth and the welfare of UMKM in Jambi City. Using a quantitative approach and SmartPLS software for data analysis, the research examines how these financial factors contribute to business development and overall well-being. The findings reveal that all three financial variables financial inclusion, access, and attitude have a positive and significant impact on both business growth and the welfare of MSME actors. Moreover, business growth plays a mediating role, meaning it acts as a crucial bridge that strengthens the relationship between financial factors and welfare outcomes. In other words, as UMKM grow, the positive effects of good financial practices become more evident in improving entrepreneurs' quality of life. These results highlight the importance of promoting financial literacy and access among small business owners. Therefore, it is recommended that government bodies and financial institutions actively support financial inclusion programs, improve financial access, and nurture a healthy financial attitude. Such efforts are essential to ensure the sustainable growth of UMKM and their meaningful contribution to the local economy.